KINETICS OF EDIBLE OILS PHYSICAL REFINING - Iuliana Vintila (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry, 2010)
Physical refining of edible oils is a valuable industrial processing which removes the minor compounds without chemical reagents involvement, based on the selective distillation process of the volatile compounds with high pressure steam at temperatures below 200 °C. Efficient removal of the minor compounds, which are considered as impurities in refined edible oils, is realized in the industrial practice both with the distillation and adsorption operation in the physical refining process. The paper presents the kinetics equation involved in a new optimization algorithm used to estimate the time-temperature dependency in the selective distillation process and adsorption kinetics equation.